The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1994
DOI: 10.1111/j.1432-1033.1994.tb18683.x
|View full text |Cite
|
Sign up to set email alerts
|

Human β1,4 galactosyltransferase and α2,6 sialyltransferase expressed in Saccharomyces cerevisiae are retained as active enzymes in the endoplasmic reticulum

Abstract: Biosynthesis and intracellular transport of recombinant human full-length Pl,4 galactosyltransferase (GT) and full-length a2,6 sialyltransferase (ST) were investigated in Saccharomyces cerevisiae. Recently, enzymic activity of recombinant GT (rGT) in crude homogenates of S. cerevisiae could successfully be demonstrated [Krezdorn, C . , Watzele, G., Kleene, R. B., Ivanov, S. X. & Berger, E. G. (1993) Eur: J. Biochem. 212, 113-1201. In the present work, we show that, in yeast strains transformed with plasmid pDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…Bound antibody was detected by peroxidase-conjugated anti-sheep immunoglobulin and enhanced chemiluminescence. Previous studies have demonstrated that ␤1,4-galactosyltransferase and ␣2,6-sialyltransferase can be expressed in S. cerevisiae as active enzymes (33,34) and here we demonstrate that wild-type GnTI can also be expressed as an active enzyme. The GnTI C123R mutant showed no activity in the GnTI null background of yeast, directly demonstrating that a Cys 123 to Arg 123 substitution results in loss of GnTI activity.…”
Section: Figsupporting
confidence: 78%
“…Bound antibody was detected by peroxidase-conjugated anti-sheep immunoglobulin and enhanced chemiluminescence. Previous studies have demonstrated that ␤1,4-galactosyltransferase and ␣2,6-sialyltransferase can be expressed in S. cerevisiae as active enzymes (33,34) and here we demonstrate that wild-type GnTI can also be expressed as an active enzyme. The GnTI C123R mutant showed no activity in the GnTI null background of yeast, directly demonstrating that a Cys 123 to Arg 123 substitution results in loss of GnTI activity.…”
Section: Figsupporting
confidence: 78%
“…When the intact full-length human ␤-1,4-galactosyltransferase or ␣-2,3-sialyltransferase were expressed in S. cerevisiae, the active enzymes appeared to be retained in the endoplasmic reticulum (21). While the former studies (15,16) suggest that mammalian Golgi-targeting domains can be used in S. cerevisiae, the latter do not (21).…”
Section: Discussionmentioning
confidence: 99%
“…Rat liver Gal@14)GlcNAc a-2,6-sialyltransferase (Boehringer Mannheim) had an activity of 0.25 U/ml; one unit (U) of enzyme activity is defined as the amount of enzyme catalyzing the transfer of 1 pmol NeuSAc/min using the incubation conditions as indicated below and 1 as an acceptor at a concentration of 2 mM. A crude preparation of recombinant full-length human liver Gal@ -4)GIcNAc a-2,6-sialyltransferase, with an activity of 3.5 niU/rnl when assayed with 2 mM 1, was isolated from a Saccharomyces cerevisiae cell culture as previously described [12]. This enzyme was tested without purification, since no interfering endogenous sialyltransferase activity is present in yeast cells.…”
mentioning
confidence: 99%